IUDEX NOVUS - ON THE METAMORPHOSIS OF THE SERBIAN JUDICIARY THROUGH ALLEGORY OF THE OFFICIAL ROBES - Tešić, Nenad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
The judicial robe is much more than an adornment and article of clothing; it is a powerful symbol of the values and principles inherent in the judicial function. Its significance transcends the practical and ceremonial, serving as a visual and cultural marker of the judiciary’s independence, impartiality, integrity and dignity. By wearing the robe, judges set aside personal bias and affiliations reinforcing the principle that justice is blind to individual differences, and that the law applies equally to all, regardless of race, gender or social status. It serves as a reminder to both judges and the public of the separation of powers and the profound significance of the judicial process and the decisions being rendered. By creating a visual distinction between the individual and the institution they represent, it reinforces the idea that the judge’s authority derives from rule of law and other fundamental legal and ethical principles. Finally, the robe is a symbol of public trust. For the community, it inspires confidence in the fairness and objectivity of the judicial process, thereby reinforcing the legitimacy of the courts as institutions of justice. Advocating the introduction of official robes in the Serbian judiciary as part of the comprehensive judicial reform is driven by more than just the need for a neat and uniform wardrobe. Rather, it is a powerful allegory with a much deeper content about the judicial metamorphosis, signifying true transformation through the adoption of core values and principles that underlie the judicial system in democratic society. Judicial robes are not a value in themselves if we do not understand them as one of the elements in the construction of a new social pattern about the judiciary system and the holders of judicial functions. According to the author, in the Serbian judiciary, it is essential to promote an independent and impartial administration of justice, personified by the iudex novus - the new holder of the judicial function - who is accepted by social consensus as the guardian of the public interest, the dignity and the integrity of the judiciary.